(untitled) (Journal of Pakistan Orthopaedic Association, 2014)
Objective: To determine the efficacy of early hip spica cast application for the management of femur shaft fractures in children. Material and Methods: This descriptive study was carried out in the Department of Orthopaedic Surgery, Nishtar Hospital, Multan from April 2008 to October 2008. Children with closed non-comminuted fracture of the shaft of femur, presenting in emergency orthopaedic department within 24-48 hours of injury were selected in the study. Results: Mean age of the children was 5.4±1.76 years. Male to female ratio was 2.6:1. There was no complication of angular deformity or LLD in children of age 2–5 years. While in 6–10 years age group, angular deformity was observed in 3 cases and shortening was observed in 3 cases. Outcome after removal of spica cast was satisfactory in 100% children of 2–5 years and 78.3% satisfactory results achieved in children between 6–10 years of age. Conclusion: Early hip spica cast immobilization is effective easy method for stabilization femur shaft fractures in children. Key Words: Femur, Fracture, traction, Spica cast.